Growth Characters and Performance of BARI SP- 10 and BARI SP-11: The Newly Released High Yielding Sweet Potato Varieties in Bangladesh - Mohanta, Haridas Chandra; Bhuiyan, Md. Khalilur Rahman; Goswami, Biresh Kumar; Hossain, Mohammad; Noor, Shamsun; Attaluri, Sreekanth (JOURNAL OF ROOT CROPS, 2016)
Abstract This article reports the yield performance in the regional and farmer’s field trials of two sweet potato genotypes viz., ‘H8’-a clonal hybrid developed from open cross with BARI SP-6, BARI SP-7, BARI SP-9 and ‘SP-613’-a clonal hybrid developed from open cross with BARI SP-7, BARI SP-8, BARI SP-9 which were released as ‘BARI SP-10’ and ‘BARI SP-11’ respectively by the National Seed Board (NSB) of Ministry of Agriculture (MOA), Bangladesh in 2013. The leaf of BARI SP-10 is green, complete and non-serrated, edge of leaf, leaf vine, petiole and stem slightly pinkish. Tuber is large sized with light brown skin and light yellow flesh. The leaf of BARI SP-11 is light green, non-serrated, heart shaped, leaf vein, petiole and stem clearly pink colored. Tuber is medium to large sized with reddish-pink skin and flesh creamy-yellow. The tuber yield potential of two varieties varied between 35 and 40 t ha-1 and was better to previously released varieties in Bangladesh. Dry matter (%) of BARI SP-10 and BARI SP-11 were 28.11 % and 35.44 % respectively. These two varieties also contain 400-500 IU/100g beta carotene. Keywords: Sweet potato, Bangladesh